Metal Salts and Surfactant Interaction for Anionic Surfactant Detection: Investigation on Different Types of Surfactant - Tan, K Reen; Hashim, Nor Haslina (Progress in Engineering Application and Technology, 2023)
The common method for anionic surfactant detection is by using methylene blue active substance (MBAS) but this method is tedious and time-consuming due to the repeated extraction with toxic chloroform. Therefore, the purpose of this study is to look into the interaction between the metal salts and surfactant that was proposed and the anionic surfactant without using liquid-liquid extraction. Reagents like Sodium Dodecyl Sulfate (SDS), Copper (II) bromide and Triethylamine (TEA) was prepared and the absorbance was measured using a UV-Vis spectrophotometer after the sample solution of different concentration of SDS, Copper (II) Bromide and TEA were freshly prepared. As a result, Copper (II) Bromide shown good interaction against anionic surfactant (SDS) and a calibration graph of absorbance against concentration with  was plotted. The  value indicates that the value of absorbance is completely explained by the concentration of anionic surfactant. Different types of surfactant like Tween 20 and Triton X-100 (non-ionic) and DDAB (cationic) were also been tested. With the equation y = 0.0812x + 0.05 obtained from the calibration graph, final concentration for all types of surfactant which are Tween 20, Triton X-100 and DDAB including SDS were calculated. It shows that Copper (II) Bromide metal is only had a good response with anionic surfactant (SDS) and shows negative responses to non-ionic surfactant (Tween 20 and Triton X-100) and cationic surfactant (DDAB). This selectivity of surfactant types experiment indicates that the Copper (II) Bromide can be one of the possible metal ions used specifically for anionic surfactant detection and qualification.